Constitutional Reform in Bangladesh: Exploring the Agenda (Northern University Journal of Law, 2014)
The Bangladeshi brand of democracy has caused some horrible nightmares in recent times. Though democracy in Bangladesh has got a certain degree of consolidation during the last eighteen years, she could not make significant progress in consolidating her democratic institutions.1 Over the years Bangladesh has gone through a phase of illiberal democracy with the politicians behaving autocratically, rewarding political supporters and punishing the opposition. Partisan, financial and personal interests curbed the bureaucracy, judiciary, police or even the legislature.2 Disorder became the order, irregular the regular, and Machiavellism the political culture.3 On the other hand, the concept of separation of power has got a violent blow in the Constitution of Bangladesh. What the Constitution has done can very well be described as assignment of powers of the Republic to the three organs of the Government.4 Concentration of power in the hands of Prime Minister resulted in paralyzing both the judiciary and legislature with leviathan omnipotence of the executive. Todays Bangladesh may well be termed a one legged state while the theory of separation of power contemplates a three legged one. Much water has already flown by and considerable amount of silt has filed up on this issue. Someone sought overnight purified democracy suitable to the genius of the people of Bangladesh while some other relentlessly asserted their absolute faith in West Ministerial Democracy and advocated for going slow, giving democracy a chance to learn from trial and error. DOI: http://dx.doi.org/10.3329/nujl.v1i0.18524 Northern University Journal of Law Vol.1 2010: 39-50